消失与变迁的三峡城镇空间 ：以贾樟柯和章明的电影为例 = Disappearing and changing space in the towns of the Three Gorges : a case study on Jia Zhangke and Zhang Ming's movies - 梁祖儿 Liang, Zuer (Nanyang Technological University, 2022)
改革开放开启了中国大规模的经济改革，使中国部分地区得到了发展，逐渐走向了现代化。发展过程中处于乡村和城市中间的小城镇是一个不可忽视的空间。它间接受到了农村或城市发展的影响，同时也被建造生产。这时代崛起的第六代导演捕捉了空间中的变化，叙事上也产生了空间转向。他们将自身对小城镇的变迁的理解呈现于影像中。 本文以贾樟柯和章明的电影为切入点，探讨电影影像如何呈现消失和变迁的三峡小城镇空间。三峡工程作为规模巨大的国家现代化工程，对小城镇空间的影响是具有代表性的。因此，本文聚焦于电影中的消失和变迁小城镇空间，以影片中的空间叙事为分析方向，从中剖析导演如何呈现他们对空间变迁的理解。 The Chinese Economic Reform (“gaige kaifang”) has contributed to the development and modernization of China. The Small Town, which is an important link between the cities and rural areas, is a space that cannot be ignored. While being built under national development schemes, it is also affected by the development of cities and rural areas. The sixth-generation film directors who emerged in this era also captured the spatial changes of these small towns. They present their own understanding of the changes in small towns in their films using the method of space narrative. This paper selects Jia Zhangke's “Still Life” and “Platform”, and Zhang Ming's “In Expectation” and “Weekend Plot” as analytical representatives to explore how film images present the disappearing and changing space of the Three Gorges small towns. The Three Gorges Project, as a national modernization project of enormous scale, is representative of its impact on the space of small towns. Therefore, this paper focuses on the disappearing and changing small town spaces in the films by taking the spatial narratives in the films as the direction of analysis, from which I analyse on the directors’ presentation of their understanding on spatial changes.